2010
DOI: 10.1063/1.3482008
|View full text |Cite
|
Sign up to set email alerts
|

Logarithmic correlators in nonrelativistic conformal field theory

Abstract: We show how logarithmic terms may arise in the correlators of fields which belong to the representation of the Schrödinger-Virasoro algebra (SV) or the affine Galilean Conformal Algebra (GCA). We show that in GCA, only scaling operator can have a Jordan form and rapidity cannot. We observe that in both algebras logarithmic dependence appears along the time direction alone.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…Analogous representations can also be considered for the Schrödinger and conformal Galilean algebras and their sub-algebras. Then, it becomes necessary to consider simultaneously the scaling dimensions x, ξ and the rapidities γ as matrices [41,42,43,57,37]. From the Lie algebra commutators it can then be shown that these characteristic elements of the scaling operators are simultaneously Jordan [37].…”
Section: Examplementioning
confidence: 99%
“…Analogous representations can also be considered for the Schrödinger and conformal Galilean algebras and their sub-algebras. Then, it becomes necessary to consider simultaneously the scaling dimensions x, ξ and the rapidities γ as matrices [41,42,43,57,37]. From the Lie algebra commutators it can then be shown that these characteristic elements of the scaling operators are simultaneously Jordan [37].…”
Section: Examplementioning
confidence: 99%
“…Replacing in the generators (4) the scaling dimension x by a 2 × 2 Jordan matrix, the Schrödinger Ward identities (or co-variance conditions) can be written down for the three two-point functions (12). The result is, in d ≥ 1 dimensions [28]…”
Section: Schrödinger Algebramentioning
confidence: 99%
“…The best-known special cases of such symmetry algebras are the Schrödinger algebra and the conformal Galilei algebra (CGA), both to be defined below. The natural question arises as to whether logarithmic correlators may be found for such NRCFTs [19][20][21], for a recent review see [22]. The answer is affirmative.…”
Section: Introductionmentioning
confidence: 99%
“…In 1 + 1 dimensions, CGA is even more special since it has an infinite-dimensional extension (which is called 'full CGA/altern-Virasoro algebra' in the literature, contains a Virasoro sub-algebra and admits two independent central charges [38]) which in turn can be obtained fully from contraction [39,40]. This infinite-dimensional extension of the CGA is almost solvable [41], a property which helps to investigate logarithmic representations and holographic realisation easily [19,20].…”
Section: Introductionmentioning
confidence: 99%